Competitive Groups as Cognitive Communities: The Case of Scottish Knitwear Manufacturers Revisited - PORAC, Joseph F. (Institutional Knowledge at Singapore Management University, 2011)
In this paper we reflect on the contribution of our 1989 article ‘Competitive Groups as Cognitive Communities: The Case of Scottish Knitwear Manufacturers’. We begin by recalling our backgrounds and motivations as collaborators on the project, and then discuss recent developments in the Scottish Borders knitwear industry. Noting that the industry has suffered continual decline in the twenty years since we published our paper, we suggest that the case still raises issues that remain open questions in the field despite the significant efforts by management researchers in recent years to understand the sources of industrial decline and revitalization. We outline what we feel are gaps in the existing literature and then end with the suggestion that these gaps are likely to be addressed only through multidisciplinary research that integrates resource, power, and cognitive theories of industrial dynamics.